Free Roast Pig at Open Day: All you can eat will not attract South Auckland Pacific Islanders to University - Brown Pulu, Teena (Te Kaharoa, 2014)
<p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">I kid you not. This is a time in Pacific regional history where as a middle-aged Tongan woman with European, Maori, and Samoan ancestries who was born and raised in New Zealand, I teach students taking my undergraduate papers how not to go about making stereotypical assumptions. The students in my classes are mostly Maori and Pakeha (white, European) New Zealanders. They learn to interrogate typecasts produced by state policy, media, and academia classifying the suburbs of South Auckland as overcrowded with brown people, meaning Pacific Islanders; overburdened by non-communicable diseases, like obesity and diabetes; and overdone in dismal youth statistics for crime and high school drop-outs. And then some well-meaning but incredibly uninformed staff members at the university where I am a senior lecturer have a bright idea to give away portions of roast pig on a spit to Pacific Islanders at the South Auckland campus open day. <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Who asked the university to give us free roast pig? Who asked us if this is what we want from a university that was planted out South in 2010 to sell degrees to a South Auckland market predicted to grow to half a million people, largely young people, in the next two decades? (AUT University, 2014). Who makes decisions about what gets dished up to Pacific Islanders in South Auckland, compared to what their hopes might be for university education prospects? To rephrase Julie Landsman’s essay, how about “confronting the racism of low expectations” that frames and bounds Pacific Islanders in South Auckland when a New Zealand university of predominantly Palangi (white, European) lecturers and researchers on academic staff contemplate “closing achievement gaps?” (Landsman, 2004). <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Tackling “the soft bigotry of low expectations” set upon Pacific Islanders getting into and through the university system has prompted discussion around introducing two sets of ideas at Auckland University of Technology (The Patriot Post, 2014). First, a summer school foundation course for literacy and numeracy on the South campus, recruiting Pacific Islander school leavers wanting to go on to study Bachelor’s degrees. Previously, the University of Auckland had provided bridging paths designed for young Pacific peoples to step up to degree programmes (Anae et al, 2002). <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">Second, the possibility of performing arts undergraduate papers recognising a diverse and youthful ethnoscape party to an Auckland context of theatre, drama, dance, music, Maori and Pacific cultural performance, storytelling, and slam poetry (Appadurai, 1996). Although this discussion is in its infancy and has not been feasibility scoped or formally initiated in the university system, it is a suggestion worth considering here. <p style="margin: 12px 0px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;">My inquiry is frank: Why conflate performance and South Auckland Pacific Islanders? Does this not lend to a clichéd mould that supposes young Pacific Islanders growing up in the ill-famed suburbs of the poor South are naturally gifted at singing, dancing, and performing theatrics? This is a characterisation fitted to inner-city Black American youth that has gone global and is wielded to tag, label, and brand urban Pacific Islanders of South Auckland. Therefore, how are the aspirational interests of this niche market reflected in the content and context of initiatives with South Auckland Pacific Islander communities in mind?